Amtree Protocol Enhancement by Multicast Tree Modification and Incorporation of Multiple Sources - Al‐Sharafi, Ali Mohammed Ali (2008)
Multicasting is a process of sending packets from one source (multiple sources) to multiple destinations. In mobile environment, when the source is mobile and migrates to a new location, the multicast tree needs to be rebuilt. AMTree is an active network based protocol intended to make the sending packets to the tree after source migration an efficient process without much modifications to the multicast tree. It is separated into three phases: 1) construction of multicast tree. 2) Handoff process. 3) Optimization Process. In AMTree protocol, after source migration, handoff latency is computed from the time of reconnecting to a new base station until finding nearest core to the mobile source. This process takes a long time and the number of messages sent is at least equal to the number of cores in the tree. In optimization, the number of nodes that requesting optimization is high. This means the time of optimization process is also high. In addition, AMTree protocol is proposed for multicast with a single source. This thesis proposes some techniques to enhance the AMTree protocol. First we propose two algorithms to improve the handoff process in AMTree protocol. Second we introduce a new method to construct the multicast tree in AMTree protocol. Third technique is incorporating multiple sources in AMTree protocol. This is an extension to AMTree Protocol. The results from experiments show that handoff latency using the new algorithms is much lower than using AMTree handoff procedure in both cases, i.e. when the source connects to a subscribed base station or not subscribed base station. By modifying the multicast tree, the number of nodes to be optimized was reduced. Also the optimization time was minimized. Incorporation of multiple sources in AMTree protocol resulted with minimized end‐to‐end latency after handoff and after optimization.